Guanxin Xiaoban capsules could treat atherosclerosis by affecting the gut microbiome and inhibiting the AGE–RAGE signalling pathway. Issue 5 (17th May 2022) - Dongliang, Yin; Yang, Rong; Peng, Sha; Deng, Jing; Huo, Yanjie; Deng, Zhe; Yau, Yuenming; Liu, Jianhe; Liao, Duanfang; Cheng, Choufu
Abstract : Introduction. Atherosclerosis is a chronic disorder in which plaque builds up in the arteries and is associated with several cardiovascular and cerebrovascular diseases such as coronary artery disease, cerebral infarction and cerebral haemorrhage. Therefore, there is an urgent need to discover new medications to treat or prevent atherosclerosis. Hypothesis/Gap Statement. The active components of Guanxin Xiaoban capsules may have an effect on the gut microbiome of patients with atherosclerosis and have a role in their therapeutic targets. Aim. The aim of this study was to identify genes and pathways targeted by active ingredients in Guanxin Xiaoban capsules for the treatment of atherosclerosis based on network pharmacology and analysis of changes to the gut microbiome. Methods. Mice were treated with Guanxin Xiaoban capsules. The 16S rDNA genome sequence of all microorganisms from each group of faecal samples was used to evaluate potential structural changes in the gut microbiota after treatment with Guanxin Xiaoban capsules. Western blotting and real-time quantitative PCR were used to detect gene targets in aortic and liver tissues. Haematoxylin and eosin staining was used to observe improvements in mouse arterial plaques. Results. The gut microbiota of atherosclerotic mice is disturbed. After Guanxin Xiaoban treatment, the abundance of bacteria in the mice improved, with an increase in the proportion of Akkermansia and a significant decrease in the proportion of Faecalibaculum . The main ingredients of Guanxin Xiaoban capsules are calycosin, liquiritin, ferulic acid, ammonium glycyrrhizate, aloe emodin, rhein and emodin. The core genes of this network were determined to be glutathione S -transferase mu 1 (GSTM1), vascular endothelial growth factor A (VEGFA) and cyclin-dependent kinase inhibitor 1A (CDKN1A). The compound–target gene network revealed an interaction between multiple components and targets and contributed to a better understanding of the potential therapeutic effects of the capsules on atherosclerosis. In addition, expression of the AGE–receptor for the AGE (RAGE) pathway was significantly inhibited and the mice showed signs of arterial plaque reduction. Guanxin Xiaoban capsules may improve atherosclerosis and reduce the plaque area by inhibiting the AGE-RAGE signalling pathway to delay the development of atherosclerosis. This mechanism appears to involve changes in the gut microbiota. Therefore, Guanxin Xiaoban capsules have potential value as a treatment for atherosclerosis.